PENGARUH LUMPUR LAUT DAN PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL MELON PADA TANAH GAMBUT - musni, safriadi (Fakultas Pertanian Universitas Tanjungpura, 2019)
This study aims to determine the effect of sea mud and NPK fertilizer on the growth and yield of melon plants and to find out the interaction between sea mud and NPK fertilizers against growth and melon yield in peat soil. The research was carried out from January to May 2018, in the experimental garden of the Faculty of Agriculture, Tanjungpura University. The method used is a Complete Accurate Design (CRD) of two factors consisting of sea mud (l) with 4 levels namely l0 = 0 kg / plant, l1 = 0.6 kg / plant, l2 = 1.2 kg / plant, l3 = 1.8 kg / plant and NPK fertilizer factor (p) with 3 levels, namely p0 = 16.5 g / plant, p1 = 22.5 g / plant, p2 28.5 g / plant. Observation variables include, number of leaves, amount of chlorophyll, number of flowers, weight of dried plants, fruit diameter and weight. The results showed that the application of 1.2 kg of sea mud/plant was the best for growth and yield of melons in peatlands and NPK fertilizers of 22.5 g / plant was the best dose for dried plants variable, and there was an interaction between of sea mud and NPK fertilizer on variable amounts of chlorophyll and dry weight of melon plants in peat soil. Keywords: melons, NPK, peat, sea mud